Jesus Our healer: Experience of Christians in Indonesia - Daniel Ronda (Jurnal Jaffray, 2023)
This paper discusses Jesus as a healer in C&MA teaching and how this teaching is lived in Asian countries such as Indonesia. The goal is to understand its doctrine and relevance in the church's life, especially the C&MA churches worldwide. Divine healing is a characteristic of Simpson’s teaching that should still be lived out in church life today. The Bible’s teaching about divine healing is not aimed at healing from suffering solely but is aimed at glorifying God and preaching the gospel of salvation. A church that is faithful in preaching the gospel will not stop practising healing prayers for those who ask to be prayed for their healing. Likewise, the church must be an agent of healing both physically and emotionally for communities that are facing various diseases.